2019
DOI: 10.1038/s41598-019-47208-2
|View full text |Cite|
|
Sign up to set email alerts
|

Study on the Visualization of Pigment in Haematococcus pluvialis by Raman Spectroscopy Technique

Abstract: As an ideal raw material for the production of astaxanthin, H . pluvialis was drawing attention during the last few years, there are some research topics initiated to find out the synthetic pathway of astaxanthin in H . pluvialis . In this study, confocal microscopic Raman technology was utilized to analyze the point-by-point mapping for H . pluvialis , and the visualization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…Although it has the same chemical formula as ASTA, its physiological function, for example, the ability to scavenge free radicals, is far less than that of ASTA ( Capelli et al., 2013 ). Haematococcus pluvialis (a freshwater unicellular microalga) is one of the most effective organisms for the production of ASTA ( Shao et al., 2019 ). It has been shown that H. pluvialis can produce a large amount of ASTA under stress conditions, such as high temperature, light, and high salinity ( Sarada et al., 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although it has the same chemical formula as ASTA, its physiological function, for example, the ability to scavenge free radicals, is far less than that of ASTA ( Capelli et al., 2013 ). Haematococcus pluvialis (a freshwater unicellular microalga) is one of the most effective organisms for the production of ASTA ( Shao et al., 2019 ). It has been shown that H. pluvialis can produce a large amount of ASTA under stress conditions, such as high temperature, light, and high salinity ( Sarada et al., 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…S9). These three bands originate from (1) a rocking vibration of the molecule's methyl component (1015 and 1014 cm -1 ) 20 , (2) from C-C single-bond stretch vibrations (1158 cm -1 ) 21,22 and (3) C=C stretching vibrations (1525 and 1518 cm -1 ) of the molecule's backbone 20,22,23 . Other Raman bands elicited by the lasers were at 910 and 908 cm -1 and considered as C-C symmetric stretch 24 .…”
Section: Fourier-transform Infrared Spectroscopy and Raman Spectroscopymentioning
confidence: 99%
“…Over the past two decades, not many studies have been published covering nonlinear Raman techniques ( Figure 2 A), but there is undoubtedly interest in this area of research, which is evidenced by the successful application of CARS for the label-free visualization of lipid, protein, and nucleic acid distribution in cells [ 60 , 62 ]; pigments in living cells [ 63 ]; and skin tissues [ 64 ]. The CARS technique is of particular importance in the field of cancer cell identification and diagnosis research [ 65 , 66 , 67 ].…”
Section: Introductionmentioning
confidence: 99%